2022
DOI: 10.3390/molecules27113562
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Variation of Amino Acid Contents and Identification of Sterols in Xinyang Mao Jian Green Tea

Abstract: As important biomolecules in Camellia sinensis L., amino acids (AAs) are considered to contribute to the overall green tea sensory quality and undergo dynamic changes during growth. However, limited by analytical capacity, detailed AAs composition in different growth stages remains unclear. To address this question, we analyzed the dynamic changes of 23 AAs during leaf growth in Xinyang Mao Jian (XYMJ) green tea. Using amino acid analyzer, we demonstrated that most AAs are abundant on Pure Brightness Day and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The heatmap and clustering analysis demonstrated that the 22 compounds could be grouped into three categories ( Figure 4 e). Six of these compounds were identified as key differential non-volatile compounds in SG, such as the umami amino acids (Thea and Asn), as well as the bitter-tasting (Glu, EC, EGC, and C) compounds [ 41 , 42 ]. A total of 7 non-volatile compounds, including EGCG, Trp, Pro, Arg, GABA, Phe, and Leu, were identified as key differential non-volatile compounds in 1G.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heatmap and clustering analysis demonstrated that the 22 compounds could be grouped into three categories ( Figure 4 e). Six of these compounds were identified as key differential non-volatile compounds in SG, such as the umami amino acids (Thea and Asn), as well as the bitter-tasting (Glu, EC, EGC, and C) compounds [ 41 , 42 ]. A total of 7 non-volatile compounds, including EGCG, Trp, Pro, Arg, GABA, Phe, and Leu, were identified as key differential non-volatile compounds in 1G.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 non-volatile compounds, including EGCG, Trp, Pro, Arg, GABA, Phe, and Leu, were identified as key differential non-volatile compounds in 1G. These compounds were primarily composed of sweet and umami-tasting free amino acids [ 42 ]. Nine non-volatile compounds, including GA, GC, CG, Que, Kac, Que-rut, Ile, Ser, and Val, were identified as key differential non-volatile compounds in 2G.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in its fragmentation pathway (Supporting Information Figure S1‐3), a series of characteristic fragment ions at m/z 465.33783 Da [M‐H‐CO 2 ‐H 2 O] − and 405.31676 Da [M‐H‐CH 3 COOH] − were produced by losing CO 2, H 2 O, and CH 3 COOH from ion at m/z 527.37464 Da, respectively. By combination with the related literature and the secondary fragment ion information of the reference standard, compound 75 was identified as pachymic acid in this study [21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…The compositions and abundance of FAAs are of much importance to the formation of food aroma and taste, which are the precursors of many volatile compounds (Hu et al., 2021; Pereira et al., 2021). According to their taste characteristics, FAAs can be divided into sweet (Gly, Ser, Ala, Pro, Thr, Cys, and Met), bitter (Arg, His, Ile, Leu, Phe, Lys, Tyr, and Val), and umami (Asp, Glu) ones (Huang et al., 2020; Sun et al., 2022). Aliphatic and aromatic alcohols, also known as higher alcohols or fusel alcohols, are predominantly formed by yeast from α‐keto acids, involving degradation of amino acids (AAs) via the Ehrlich pathway, contributing to the alcoholic flavor (Cordente et al., 2012).…”
Section: Introductionmentioning
confidence: 99%